Leadership under pressure tactics from the front line - Stewart, Bob Colonel (IG library, 2009)
In Leadership under Pressure, Bob Stewart draws on his experiences in the army and in business, using those experiences to illustrate the key attributes of a leader. In this timely and personal view of leadership, readers learn how to maintain morale in tough times, deal with a crisis, show courage to colleagues, and lead others by example. Stewart's personal experiences including accounts of planning a VIP visit and negotiating with a warlord.